2020
DOI: 10.1155/2020/2562979
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Improves IBS Visceral Hypersensitivity by Inhibiting the Activation of Astrocytes in the Medial Thalamus and Anterior Cingulate Cortex

Abstract: Objective. To explore whether the effect of electroacupuncture (EA) on visceral hypersensitivity (VH) in rats with irritable bowel syndrome (IBS) is related to the changes of astrocyte activation in the medial thalamus (MT) and anterior cingulate cortex (ACC). Method. Male Sprague-Dawley rats were randomly divided into the normal control (NC) group, model control (MC) group, electroacupuncture (EA) group, and fluorocitrate (FCA) group. A model of visceral hypersensitivity was established by neonatal colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The analgesic effect of EA on visceral hypersensitivity has been extensively demonstrated (40)(41)(42)(43)(44), and the results of our study are consistent with this. EA reduced AWR scores and increased PWT, indicating that EA attenuated the visceral sensitization and peripheral mechanical hyperalgesia of PI-IBS.…”
Section: Discussionsupporting
confidence: 91%
“…The analgesic effect of EA on visceral hypersensitivity has been extensively demonstrated (40)(41)(42)(43)(44), and the results of our study are consistent with this. EA reduced AWR scores and increased PWT, indicating that EA attenuated the visceral sensitization and peripheral mechanical hyperalgesia of PI-IBS.…”
Section: Discussionsupporting
confidence: 91%
“…In a rat model of IBS, EA attenuated visceral hyperalgesia by inhibiting the enhanced excitability of colon dorsal root ganglion neurons (29). Zhao et al found that EA improved IBS visceral hypersensitivity by inhibiting the activation of astrocytes in the medial thalamus and anterior cingulate cortex (30). In a controlled clinical study with 7 patients with IBS-D, TEA increased the threshold for rectal sensation of gas, desire to defecate, and pain (31).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent report indicated that inhibiting the activation of astrocytes in the medial thalamus and anterior cingulate cortex would get involved in EA alleviating IBS VH. It implied that the central mechanism should not be neglected in the future research ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%